Unlocking the potential of smart grid technologies with behavioral science - Sintov, Nicole D.; Schultz, P. Wesley (Frontiers in Psychology, 2015)
Smart grid systems aim to provide a more stable and adaptable electricity infrastructure, and to maximize energy efficiency. Grid-linked technologies vary widely in form and function, but generally share common potentials: to reduce energy consumption via efficiency and/or curtailment, to shift use to off-peak times of day, and to enable distributed storage and generation options. Although end users are key players in these systems, they tend to be overlooked. Behavioral science is therefore key to engaging end-users and maximizing the impact of smart grid technologies. In this paper, we highlight several ways in which behavioral science can be applied to better understand and engage customers in smart grid systems.